ANALISIS KESELAMATAN PADA RANCANGAN INSTALASI INSINERATOR LIMBAH PROPELAN - Wely Pasadena; Timbul Siahaan; Pujo Widodo (Jurnal Education and Development, 2022)
Work safety on a job is very necessary, as well as in the propellant waste treatment plant. The Incinerator functions as a propellant waste treatment and interconnected with other supporting facilities such as cutting tools, conveyors and also propellant waste material. So that the layout in the incinerator facility does not cause a potential accident, it is necessary to carried out a safety analysis on the layout design of the facility. The purpose of the research was safety aspects of the incinerator installation. In the aspect of safety analysis, the dominant hazard was identified in the cutting process which can cause an accident to cut hands and be electrocuted. The layout of the installation proposed by considering the safety aspect, it was found that the required space requirement was 15mx20m. initial planning, hazards or accidents can be prevented or reduced.